2022
DOI: 10.1038/s41467-021-27949-3
|View full text |Cite
|
Sign up to set email alerts
|

Host receptor-targeted therapeutic approach to counter pathogenic New World mammarenavirus infections

Abstract: Five New World mammarenaviruses (NWMs) cause life-threatening hemorrhagic fever (HF). Cellular entry by these viruses is mediated by human transferrin receptor 1 (hTfR1). Here, we demonstrate that an antibody (ch128.1/IgG1) which binds the apical domain of hTfR1, potently inhibits infection of attenuated and pathogenic NWMs in vitro. Computational docking of the antibody Fab crystal structure onto the known structure of hTfR1 shows an overlapping receptor-binding region shared by the Fab and the viral envelope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…26 In the same study, we also showed that ch128.1/IgG1 has minimal toxicity to human committed hematopoietic progenitor cells (including erythroid progenitors) in vitro. 26 Therefore, the combination of bortezomib and ch128.1/IgG1 or lenalidomide and ch128.1/IgG1 would likely present side effects that can be controlled and the risks they convey in humans mitigated. A limitation of using mice in our studies is that this species does not properly address the issue of toxicity of ch128.1/IgG1 since this antibody does not crossreact with the murine TfR1.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…26 In the same study, we also showed that ch128.1/IgG1 has minimal toxicity to human committed hematopoietic progenitor cells (including erythroid progenitors) in vitro. 26 Therefore, the combination of bortezomib and ch128.1/IgG1 or lenalidomide and ch128.1/IgG1 would likely present side effects that can be controlled and the risks they convey in humans mitigated. A limitation of using mice in our studies is that this species does not properly address the issue of toxicity of ch128.1/IgG1 since this antibody does not crossreact with the murine TfR1.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, we have recently shown that ch128.1/IgG1 does not inhibit transferrin binding and only partially inhibits the binding of ferritin (important for iron uptake in erythroid progenitor cells) to TfR1 26. In the same study, we also showed that ch128.1/IgG1 has minimal toxicity to human committed hematopoietic progenitor cells (including erythroid progenitors) in vitro 26. Therefore, the combination of bortezomib and ch128.1/IgG1 or lenalidomide and ch128.1/IgG1 would likely present side effects that can be controlled and the risks they convey in humans mitigated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ferritin presents higher levels in response to infection ( Sandalinas et al, 2022: ), and hemoglobin participates in iron metabolism, response to oxidative stress and inflammation and low levels are associated with a decrease in cellular immunity ( Yang et al, 2022 ). Lastly, TfR is involved in the iron metabolism and virus infection ( Hickerson et al, 2022 ), having a potential role in entry of SARS-CoV-2 ( Dai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the use of anti-TfR1 antibodies, toxicity to these normal cells expressing high levels of TfR1 is a concern. Previous studies show that antibodies containing the 128.1 variable regions bind the apical domain of TfR1 and do not inhibit the binding of transferrin to the receptor or block TfR1 internalization [ 21 , 22 , 34 , 43 ]. However, ch128.1/IgG1 partially blocks the binding of the heavy chain of ferritin (H-Ft) [ 43 ], known to bind the apical domain of TfR1 and play a role in the uptake of iron in erythroid progenitor cells [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%